SISTEM INFORMASI PENJUALAN PADA TOKO ANARMAN STORE BERBASIS WEB - Napitupulu, Devita Winda; Nainggolan, Rena; Saragih, Rijois Iboy Erwin (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
Toko Anarman Store is a toy store that sells various kinds of toys, education, and home decor. This shop still uses a manual system for sales transactions, with the process of selling goods usually still written on notes and then summarized in a sales book. The seller must check each item individually and record the results in a book to determine the number of items in the store. Therefore this web-based Sales Information System is designed to assist the sales process at the store. The purpose of this system is to increase the efficiency and effectiveness of the sales process. This system includes several important features which include product management, supplier management, and report printing. Product management includes adding, deleting, and updating product data available in the store. Printing includes printing sales reports, stock reports, consumer reports, and supplier reports. This information system is made using the Sublime Text 3 application while the programming language uses PHP, Xampp is used to run the web server, MySQL is used for database management. With this system, it is hoped that Anarman Store can improve operational efficiency and increase customer satisfaction. This system can also help in making better decisions based on accurate sales data.